An Overview on Animal Models to Boost Preclinical Research in COVID 19 (Journal of Pharmaceutical Negative Results, 2022)
The current review was undertaken by collecting data through a thorough literature search in PubMed and Google Scholar in order to identify the relevant English-language articles published on animal models for COVID-19 research. The data was obtained from articles published between 2019 and 2021. After a comprehensive review of various available articles, this review outlines the available animal models for COVID-19 and their key roles in elucidating the pathogenesis, disease transmission, and host response to the SARS-CoV-2 virus. Reports from various preclinical trials have shown the use of several animal models such as mice, hamsters, ferrets, and non-human primates (NHPs) for studying the SARS-CoV-2 infection. However, availability of an ideal animal model would help researchers in assessing the efficacy of investigational drugs before they enter clinical trials. No single animal model delineates the totality of pathogenesis or predicts interventional responses faithfully as in humans. Therefore, defining animal models and their use is deemed as a prerequisite for conducting comparative studies of vaccines and therapeutics’ efficacy so that the most promising ones advance to the next phase.